2023
DOI: 10.1108/imr-05-2022-0113
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as an innovation: a tool to improve organizational marketing performance and sustainability of international firms

Abstract: PurposeThis study aims to investigate an under-researched area, an international marketing perspective, based on international dynamic capability, environmental sustainability and organizational marketing performance in gamification and non-gamification-based organizational culture (OC). This paper deepens the understanding of gamification-based and non-gamification-based OC influence on innovation capability and environmental and organizational marketing performance through the theory of organizational creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…We have demonstrated that by improving the MGS and the decision-making process, and by articulating appropriate planning, it is possible for organizations to strengthen their innovation capability. This idea has received support from different studies (Ali et al , 2017; Shafique et al , 2022; Behl et al , 2023).…”
Section: Resultsmentioning
confidence: 95%
“…We have demonstrated that by improving the MGS and the decision-making process, and by articulating appropriate planning, it is possible for organizations to strengthen their innovation capability. This idea has received support from different studies (Ali et al , 2017; Shafique et al , 2022; Behl et al , 2023).…”
Section: Resultsmentioning
confidence: 95%
“…Hollebeek et al (2020) discussed about the social presence theory while stating that the brand association get more colourful when users connect with the brand on various virtual platforms and develop brand value. Users' perceived value get increase when they connect with the brand in an immersive Metaverse connected with XR technology (Behl et al, 2023; Buhalis et al, 2022; Rauschnabel et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These virtually wearable assets are considered a gamification activity, where consumers are associated with the brand with a feeling of pre‐ownership of the luxury product for their AVATAR. As discussed by Hsu and Chen (2018a) and Behl et al (2023), gamification marketing activities trigger consumers to perform an action in an embodied environment where they provide personal information while associated with the gamified event, such a type of information like name, address, preferences of choice of brand, the cognitive process of product selection, and so forth, are a very crucial set of information for luxury retail brands. And interaction with brands in a 3‐D environment provides a funnel system for brands to pool the consumers' valuable data while asking them to connect with the brand to use virtually wearable products for their AVATAR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamification can differentiate a firm's market offerings and affect consumer behavior; thus, designing gamification experiences is becoming an increasingly significant part of marketing strategies (Torres et al ., 2022). For example, several international service providers, including Nike, McDonald's and Bing, have successfully used gamification in their business practices (Behl et al ., 2023) and brand apps such as IKEA Studio, Amazon's AR View and Starbucks Rewards have used gamification to deliver unique brand experiences to customers (Kaur et al ., 2023). Thus, gamification is a marketing technique that allows firms to increase psychological responses to advertising, improve brand recall, expand brand awareness and foster a positive attitude toward the company (Noorbehbahani et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%